Comparing good and bad borrowing in developing countries - a study of twin cases - Andreas Freytag; Martin Paldam (Graduiertenkolleg 'Konstitutionelle Grundlagen globalisierter Finanzmärkte - Stabilität und Wandel', 2012)
Some developing countries borrow abroad and experience good growth (above 2 %), which we call good growth, while others borrow and have poor growth (below 1 %), which we label as bad growth. The data comprise all 443 available observations of borrowing for one 5-year period and average growth rates for the following 10-year period. First, we confirm the standard result: The relation between borrowing and growth is negative, but explains little of the variations in the growth rate. Second, we select a subset of 59 twins of LDCs with matching borrowing (shares of GDP) in the same period. One twin has good growth and the other bad growth. The two sets are compared over a total of 12 main indicators from different fields. The good cases occur in countries with more economic and political freedom; also they are somewhat more developed, and have fewer natural resources. While this pattern is strong between samples, it is weak within samples.
urn:nbn:de:gbv:27-20131126-140820-8
Keywords: 330; Öffentliche Schulden; Internationale Staatsschulden; Wirtschaftswachstum; Good Governance; Entwicklungsländer